Pengaruh Pembelajaran Berdiferensiasi Dan Sikap Religius Terhadap Kemampuan Berpikir Kritis Siswa Kelas X Di MAN 2 Deli Serdang - Manalu, Sri Rahmayani; Wijaya, Candra; Anas, Nirwana (Jayapangus Press, 2024)
One of the efforts of the Ministry of Education and Culture to improve the quality of education is launching the Independent Learning Curriculum, one of the characteristics highlighted in this curriculum is Differentiated Learning. Research using differentiated learning and religious attitudes was carried out in order to determine the influence of students' critical thinking abilities on buying and selling material in class The population of this study were all students of class X MAN 2 Deli Serdang consisting of 12 classes. The sampling technique used is non-probable sampling with purpose sampling. Data collection instruments are tests and questionnaires. Normality testing uses the Kolmogorov-Smirnov method and homogeneity testing uses the Levene and Barllett method. The data analysis technique is two-way analysis of variance at  = 0.05. The results of the research show: (1) there is an influence of differentiated learning on the critical thinking abilities of class X students at MAN 2 Deli Serdang. This is proven by the variable significance value (p-value) which is smaller than 0.05 (0.046 < 0.05), (2) there is a significant influence between religious attitudes and students' critical thinking abilities. This is proven by the variable significance value (p-value) which is smaller than 0.05 (0.000 < 0.05), and (3) there is no interaction between differentiated learning and religious attitudes on students' critical thinking abilities. The results of statistical analysis show that the significance value (p-value) for this interaction is 0.534 which is greater than 0.05 (0.534 > 0.05)).